A MODEL PROPOSAL FOR THE NETWORK DESIGN PROBLEM WITH HETEROGENEOUS CUSTOMER SEGMENTS AND DEMAND UNCERTAINTY ASSUMPTIONS (Third Sector Social Economic Review, 2023)
This study addresses a network design problem with horizontal collaboration between heterogeneous customer segments consisting of high-tier customers, mid-tier customers, and basic customers under the assumption of demand uncertainty. A linear integer programming model is developed for the problem. The model involves distribution channel selection, distribution planning, inventory, transshipment and assignment decisions. After the presentation of the developed mathematical model, the network design problem is solved using a general purpose solver for a case study and different scenarios derived from this case study. Then, numerical analyses were performed for the case study and scenario solutions, the functionality of the model was demonstrated and evaluations were made based on the key performance criteria. As a result of the numerical analysis, some crucial outputs have been revealed for decision makers confronted with similar decision processes. It has been observed that the absence of the option to transshipment products among top customers and from high tier customers to mid tier customers increases the total cost. As a result, horizontal cooperation built across supply chain actors can be said to improve total network cost.
Keywords: Network Design Problem; Linear Integer Programming; Customer Segmentation; Horizontal Collaboration; Inventory